To solve the equation \( 7 + y = 5(2y - 1) + 3y \), let's start by simplifying the right side.
-
Distribute the \( 5 \) on the right-hand side: \[ 5(2y - 1) = 10y - 5 \] So, the equation now looks like: \[ 7 + y = 10y - 5 + 3y \]
-
Combine the terms on the right-hand side: \[ 10y + 3y = 13y \] Thus, the equation simplifies to: \[ 7 + y = 13y - 5 \]
-
Next, we will isolate \( y \). First, subtract \( y \) from both sides: \[ 7 = 13y - y - 5 \] This simplifies to: \[ 7 = 12y - 5 \]
-
Add \( 5 \) to both sides: \[ 7 + 5 = 12y \] This gives: \[ 12 = 12y \]
-
Now divide both sides by \( 12 \): \[ y = 1 \]
Now that we have \( y = 1 \), let’s check the solution by substituting \( y \) back into the original equation.
The original equation is: \[ 7 + y = 5(2y - 1) + 3y \]
Substituting \( y = 1 \):
-
Left side: \[ 7 + 1 = 8 \]
-
Right side: \[ 5(2(1) - 1) + 3(1) = 5(2 - 1) + 3 = 5(1) + 3 = 5 + 3 = 8 \]
Both sides are equal, as \( 8 = 8 \).
Thus, the solution is confirmed: \[ \boxed{1} \]